IMPLEMENTATION OF ARTICLE 31 LOCAL RULE NUMBER 2 IN 2012 SIDOARJO DISTRICT OF SUPERVISION AND CONTROL OF THE ORGANIZATION OF PARKING IN THE DISTRICT SIDOARJO - Swandaru Widyatama (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2014)
Parking is a state in which the vehicle is stopped or does not move for a few moments and the driver left the parking place. Sidoarjo District as one of the buffer Capital City of East Java Province is an area that is experiencing rapid development and has autonomous to increase regional income. Therefore formed Sidoarjo District Regulation No. 2 of 2012 onÂ the Implementation of parking in Sidoarjo Regent and Regulation No. 35 Year 2012 on Implementation Guidelines Sidoarjo District Regulation No. 2 of 2012 on the Implementation of parking in Sidoarjo. Department of Transportation as the organizer of the parking Sidoarjo District has the task of monitoring and controlling parking. This is done to create a good public service for the people of Sidoarjo District.Keywords : Parking, Supervision and Control of Parking, Public Service